1976
DOI: 10.1104/pp.57.4.480
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Carbon Dioxide Promotion and Ethylene Inhibition of Tuberization in Potato Explants Cultured in Vitro

Abstract: the C2H4 inhibition of tuberization in vitro. The earlier work on potato stolons has been further extended to the study of the actions of CO2 and C2H4 on tuberization of sprout sections cultured in vitro. MATERIALS AND METHODSPlant Material and in Vitro Culture. Tubers of Solanum tuberosum L. var. Red La Soda which had been grown for seed were used in all experiments. On one occasion, var. White Rose was also tested. Sprout sections or stolons were obtained according to the technique described previously (16) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
16
0

Year Published

1977
1977
2006
2006

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(17 citation statements)
references
References 15 publications
(15 reference statements)
1
16
0
Order By: Relevance
“…He also showed that tuber formation was promoted by darkness and moisture. Recent evidence (16,17) suggests that elevated CO2 levels may also favor tuberization at below ground rather than above ground buds. However, tubers do not always develop even from underground buds of cuttings.…”
Section: Introductionmentioning
confidence: 99%
“…He also showed that tuber formation was promoted by darkness and moisture. Recent evidence (16,17) suggests that elevated CO2 levels may also favor tuberization at below ground rather than above ground buds. However, tubers do not always develop even from underground buds of cuttings.…”
Section: Introductionmentioning
confidence: 99%
“…Although ABA has been shown to promote tuberization in Solanum andigena (22), it inhibited cytokinin-mediated tuberization of Solanum tuberosum (7). Ethylene inhibited tuberization (11) and the role of auxin in this process has not been studied in detail (9).…”
mentioning
confidence: 99%
“…3) on treated potatoes. As the endogenous level of cytokinins did not change in the Ethrel-treated tubers, ethylene could also have prevented these compounds from acting at the subapical meristem, particularly as kinetin-induced tuberization (17,19) can be reversed by this hormone (12,13). This reversal could have been the result of an inhibition of cell division and/or starch synthesis.…”
Section: Resultsmentioning
confidence: 99%
“…They do, however, promote stolon elongation (15). Natural tuberization (12) as well as the kinetin-stimulated accumulation of starch in stolons (13) are inhibited by ethylene. Ethylene also inhibits stolon elongation and causes the development of abnormal subapical swellings (13) devoid of any appreciable starch (6).…”
mentioning
confidence: 99%